ACE2 (Angiotensin-Converting Enzyme 2), COVID-19, and ACE Inhibitor and Ang II (Angiotensin II) Receptor Blocker Use During the Pandemic: The Pediatric Perspective. Issue 1 (July 2020) - South, Andrew M.; Brady, Tammy M.; Flynn, Joseph T.
Abstract : Potential but unconfirmed risk factors for coronavirus disease 2019 (COVID-19) in adults and children may include hypertension, cardiovascular disease, and chronic kidney disease, as well as the medications commonly prescribed for these conditions, ACE (angiotensin-converting enzyme) inhibitors, and Ang II (angiotensin II) receptor blockers. Coronavirus binding to ACE2 (angiotensin-converting enzyme 2), a crucial component of the renin-angiotensin-aldosterone system, underlies much of this concern. Children are uniquely impacted by the coronavirus, but the reasons are unclear. This review will highlight the relationship of COVID-19 with hypertension, use of ACE inhibitors and Ang II receptor blockers, and lifetime risk of cardiovascular disease from the pediatric perspective. We briefly summarize the renin-angiotensin-aldosterone system and comprehensively review the literature pertaining to the ACE 2/Ang-(1–7) pathway in children and the clinical evidence for how ACE inhibitors and Ang II receptor blockers affect this important pathway. Given the importance of the ACE 2/Ang-(1–7) pathway and the potential differences between adults and children, it is crucial that children are included in coronavirus-related research, as this may shed light on potential mechanisms for why children are at decreased risk of severe COVID-19.